Clerodendranthus spicatus [Orthosiphon aristatus (Blume) Miq.] maintains uric acid homeostasis via regulating gut microbiota and restrains renal inflammation in hyperuricemic nephropathy - Wang, Yang; Li, Kaiwen; Yan, Siya; Li, Ge; Cheng, Meifang; Chen, Qian; Wu, Yuzheng; Wang, Dan; Wang, Tao (Frontiers in Pharmacology, 2024)
The kidney damage caused by the deposition of uric acid in the kidneys is of urgent need for new treatment drugs due to its complex pathogenesis. Orthosiphon aristatus (Blume) Miq. also known as Clerodendranthus spicatus, which has a significant therapeutic effect on hyperuricemia nephropathy (HN), however, the specific mechanism of its action is still unknown. sterile HN mice, without the effect of gut microbiota, the uric acid lowering, antiinflammatory, and renal fibrosis improving effects of C.spicatus were significantly reduced.Our results demonstrated that C.spicatus could reduce uric acid levels, anti-inflammatory effects, and improve HN by regulating the gut microbiota. This provides a novel scientific basis for the clinical application of C.spicatus.